The Influence of Attitude, Skill, and Knowledge Control on Employee Perfomance at PT. Astha Kencana Mulia - Yuswidyana Anita Indah Pratiwi; Tri Wahjoedi (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
The purpose of this research is to reveal the extent to which Attitude, Skill, and Knowledge control have a significant influence on the performance of employees of PT. Astha Kencana Mulia.. This research method is a quantitative, descriptive approach. The sample taken had 57 respondents. In collecting data using online questionnaires and direct observation. Data analysis techniques using PLS-SEM The research was conducted for approximately three months and explored the phenomenon of employee performance in terms of the implications of improving employee performance that is less than optimal. The findings from the study show that employee performance has increased significantly thanks to the positive impact of attitudes and skills, while knowledge does not contribute significantly and can even have a negative impact on employee performance.